Traces of War : Interpreting Ethics and Trauma in Twentieth-Century French Writing. - Davis, Colin. (Contemporary French and Francophone Cultures Series, 2018)
Traces of War examines how the trauma of the Second World War influenced the work of the brilliant generation of writers and intellectuals who lived through it.